(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Literature of each era serves as an embodiment of the past events of the history as such, novels, satires, proses are the bright tunnels between the past and the present. Days Gone By, a masterpiece created by Abdulla Qadiri, one of the most influential Uzbek writers of the last century is an evocative storyline which won the hearts of many readers. This classic origin story of the Uzbek people was written at a time of various difficulties and triumph which probably were experienced by many nations when the cultural landscape of Central Asia grappled with the countervailing forces of reform and modernity.